1997
DOI: 10.1254/jjp.75.407
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Hange-shashin-to on Irinotecan Hydrochloride-Caused Diarrhea and Its Relevance to the Colonic Prostaglandin E2 and Water Absorption in the Rat

Abstract: ABSTRACT-The possible preventive effect of Kampo medicine Hange-shashin-to (TJ-14) on chronic di arrheal symptoms induced by the administration of the anticancer agent irinotecan hydrochloride (CPT-11) was investigated in the rat. Repeated oral administrations of TJ-14 at 125 and 500 mg/kg significantly prevented the reduction in body weight and the onset of chronic diarrheal symptoms due to CPT-11 in a dose-dependent manner, even though it failed to show a definite effect on acute diarrheal symptoms. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 25 publications
1
51
0
2
Order By: Relevance
“…Specifically, the number of goblet cells in the colon crypt column increased by 49% (hyperplasia) but the number of non-goblet cells (mainly columnar absorptive cells) was decreased by 39% following treatment with CPT-11. The reduction in the number of columnar absorptive cells in the colon may help account for the reported malabsorption of water and electrolytes in the large bowel of CPT-11-treated individuals (Kase et al, 1997a).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the number of goblet cells in the colon crypt column increased by 49% (hyperplasia) but the number of non-goblet cells (mainly columnar absorptive cells) was decreased by 39% following treatment with CPT-11. The reduction in the number of columnar absorptive cells in the colon may help account for the reported malabsorption of water and electrolytes in the large bowel of CPT-11-treated individuals (Kase et al, 1997a).…”
Section: Discussionmentioning
confidence: 99%
“…Hangeshashinto is reported to have the capabilities for the protection of the gastric mucosa 7) , the antidiarrheal effect 8,9) , the anti-inflammatory effect [9][10][11] and the enhancement of large intestinal water absorption 12) . From these indications, we considered that hangeshashinto could be useful for periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, TJ-14 has been used for acute or chronic diarrhea, acute gastroenteritis, and for chronic hypoperfusion of the gastrointestinal system [24,25]. It is reported that TJ-14 is effective against diarrhea which is the side effect of chemotherapeutic agents for gastrointestinal cancers [26]. Since TJ-14 contains baicalin, an inhibitor of β-glucuronidase, a randomized trial for advanced small cell lung cancer demonstrated the effect of TJ-14 in significantly controlling grade ≧3 diarrhea caused by cisplatin/irinotecan treatment with a p value of 0.018 [27,28].…”
Section: Discussionmentioning
confidence: 99%